Association of Gestational Diabetes and Proinflammatory Cytokines (IL-6, TNF-α and IL-1β) - GELEN, Volkan; ŞENGÜL, Emin; ATİLA, Gözde; USLU, Hamit; MAKAV, Mustafa (Journal of Embryology, 2017)
Changes to proinflammatory cytokines as a result of gestational diabetes mellitus (GDM), and the pregnancy complications that these changes can cause, are of vital importance to the effective prevention and optimal management. Interleukin-6 (IL-6), interleukin-1 beta (IL-1β), and tumor necrosis factor alpha (TNF-α) are cytokines that are associated with gestational diabetes. Therefore, the aim of this review is to draw attention to the relationship between gestational diabetes and these diseases
Keywords: IL-6; TNF-α; IL-1β; GDM